2023
DOI: 10.1002/chem.202302994
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroguaiazulenide Complexes and Catalysts of Group 8–12 Transition Metals: Ligands from Renewable Feedstock Replace, even Outmatch Petrochemical Based Cyclopentadienyl Chemistry

Tobias Vollgraff,
Angelino Doppiu,
Jörg Sundermeyer

Abstract: We present an in‐depth study of the sterically demanding Cp synthon (8‐H‐GuaH)Li isolated from natural product guaiazulene as a ligand transfer reagent towards late transition metal complex precursors. The synthesis and full characterization of selected, essentially unexplored homo‐ and heteroleptic 8‐H‐guaiazulenide complexes of iron, ruthenium, cobalt, rhodium, platinum, copper and zinc are discussed in detail. In order to demonstrate their potential in catalytic applications, [(GuaH)PtMe3] was selected. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…Later studies established that this interconversion can also be induced photochemically, and the barrier to haptotropic migration was found to be 117 ± 8 kJ mol −1 [99]; in the ruthenium analogues, the barriers were found to be markedly higher [100]. In an excellent very recent publication, it was reported that hydrolithiation of guaiazulene yields the isomerically pure dihydroguaiazulenide anion, a stable and storable cyclopentadienide-type ligand ideally suited for reaction with a wide range of organometallic precursors [101]. A number of half-sandwich complexes shown in Figure 6, in particular the trimethylplatinum complex, exhibit excellent catalytic activity in alkene hydrosilylations.…”
Section: Organometallic Derivatives Of Guaiazulenementioning
confidence: 99%
See 1 more Smart Citation
“…Later studies established that this interconversion can also be induced photochemically, and the barrier to haptotropic migration was found to be 117 ± 8 kJ mol −1 [99]; in the ruthenium analogues, the barriers were found to be markedly higher [100]. In an excellent very recent publication, it was reported that hydrolithiation of guaiazulene yields the isomerically pure dihydroguaiazulenide anion, a stable and storable cyclopentadienide-type ligand ideally suited for reaction with a wide range of organometallic precursors [101]. A number of half-sandwich complexes shown in Figure 6, in particular the trimethylplatinum complex, exhibit excellent catalytic activity in alkene hydrosilylations.…”
Section: Organometallic Derivatives Of Guaiazulenementioning
confidence: 99%
“…A number of half-sandwich complexes shown in Figure 6, in particular the trimethylplatinum complex, exhibit excellent catalytic activity in alkene hydrosilylations. In an excellent very recent publication, it was reported that hydrolithiation of guaiazulene yields the isomerically pure dihydroguaiazulenide anion, a stable and storable cyclopentadienide-type ligand ideally suited for reaction with a wide range of organometallic precursors [101]. A number of half-sandwich complexes shown in Figure 6, in particular the trimethylplatinum complex, exhibit excellent catalytic activity in alkene hydrosilylations.…”
Section: Organometallic Derivatives Of Guaiazulenementioning
confidence: 99%